Microhabitat use and photoacclimation in the clownfish sea anemone Entacmaea quadricolor. (May 2014) - Dixon, Austin K.; Needham, David; Al-Horani, Fuad A.; Chadwick, Nanette E.
<x content-type="archive" xml:space="preserve">Abstract</x> Many reef-building corals photoacclimate by increasing levels of chlorophyll per microalgal cell with depth, but mechanisms of photoacclimation in coral reef sea anemones remain poorly understood. We determined variation in ambient irradiance and patterns of abundance, microhabitat use, chlorophyll and microalgal cell concentrations in clownfish sea anemones Entacmaea quadricolor from 0 to 43 m depth on a coral reef at Aqaba, Jordan, northern Red Sea. In shallow areas, anemones occupied shaded reef microhabitats exposed to significantly lower irradiance than in the adjacent open water, but on the deep reef slope they occupied unshaded habitats. Anemone abundances were the highest observed thus far in the Red Sea, and peaked at mid depth on the reef slope. Microalgal abundance in anemone tentacles increased four-fold from the shallow to deep reef, while chlorophyll-a concentrations per algal cell did not vary significantly with depth. We conclude that E. quadricolor photoacclimates using two major mechanisms: (1) occurrence in shaded microhabitats when shallow, thus reducing exposure to high irradiance, and (2) increasing microalgal abundance with depth, thereby enhancing photosynthetic efficiency at low irradiance.